Relations between organizational anthropology and traditional technologies: A conceptual approach - Abad, Andrés (2022)
This article reflects on the role of traditional technologies from the cultural, human and meaning construction approach provided by organizational anthropology. It is considered that the use of technologies has left aside traditional technologies linked to ancestral knowledge as an object of study. The ethnographic approach exposes new and future elements of research; likewise, this study reviewed relevant literature and documents from Andean, indigenous and Kichwas authors. Results suggest that traditional technologies are necessary to implement an alternative productive process that considers the human factor, which improves or adapts technologies to the labour framework. In conclusion, this research provide different answers to understanding what traditional technologies and what are their contributions.